2022
DOI: 10.3390/jmse10121957
|View full text |Cite
|
Sign up to set email alerts
|

Information Capacity of Turbulent and Absorptive Underwater Wireless Link with Perfect Laguerre–Gaussian Beam and Pointing Errors

Abstract: The model of information capacity for underwater wireless optical communication (UWOC) links with pointing errors and the carrier of perfect Laguerre–Gaussian (PLG) beam in absorbed and weakly turbulent seawater is modeled. Using this model, the influence of channel parameters on the propagation of PLG beams is numerically analyzed. We show that the pointing error significantly reduces the performance of the optical transmission system. Large topological charge and radial orders are not conducive to high infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…On the other hand, the BER rises as the receive aperture R increases in figure 7(a). The reason for this result is that the enlargement of R increases the total signal of OAM mode m 0 as well as the crosstalk of OAM modes m ≠m 0 in all channels, but the increment of the denominator in equation (11) is larger than that of the numerator, leading to an increase of the received crosstalk noise [22,43,44], hence degrading the quality of the communication. In figure 7(b), as the OAM channel number N increases, the amount of information transmitted by the communication link increases, so the average capacity of the system increases.…”
Section: Numerical Simulation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the BER rises as the receive aperture R increases in figure 7(a). The reason for this result is that the enlargement of R increases the total signal of OAM mode m 0 as well as the crosstalk of OAM modes m ≠m 0 in all channels, but the increment of the denominator in equation (11) is larger than that of the numerator, leading to an increase of the received crosstalk noise [22,43,44], hence degrading the quality of the communication. In figure 7(b), as the OAM channel number N increases, the amount of information transmitted by the communication link increases, so the average capacity of the system increases.…”
Section: Numerical Simulation and Discussionmentioning
confidence: 99%
“…Considering the transmitter power and Gaussian white noise, the signal-to-noise-and-crosstalk ratio (SNCR) received by the receiver is defined as [22,43]…”
Section: Theoretical Derivationmentioning
confidence: 99%
“…It approximates more closely to an ideal PV beam than the SPV does. In addition, researches have been conducted on the performance of a PLG beam in wireless optical communication, and it has been found that PLG can outperform other perfect vortex beams [47][48][49]. The cylindrical wave function of the PLG beam can be expressed as:…”
Section: Model and Theorymentioning
confidence: 99%
“…They validated that oceanic turbulence under salinity fluctuations and increased strength have adverse impacts on the OAM. Zhang et al [2] modeled the information capacity of UWOC links with pointing errors and the carrier of a perfect Laguerre-Gaussian (PLG) beam in weakly turbulent and absorbed seawater. Further, they numerically analyzed the impact of channel characteristics on the propagation of PLG beams.…”
mentioning
confidence: 99%